Combining Associations Between Emotional Intelligence, Work Motivation, and Organizational Justice With Counterproductive Work Behavior: A Profile Analysis via Multidimensional Scaling (PAMS) Approach - Tziner, Aharon; Fein, Erich C.; Kim, Se-Kang; Vasiliu, Cristinel; Shkoler, Or (Frontiers in Psychology, 2020)
The need for better incorporation of the construct emotional intelligence (EI) into counterproductive work behavior (CWB) research may be achieved via a unified conceptual framework . Accordingly, the purpose of this paper is to use the Profile Analysis via Multidimensional Scaling (PAMS) approach, a conceptual framework that unifies motivational process with antecedents and outcomes, to assess differences in EI concerning a variety of constructs: organizational justice, CWB, emotional exhaustion, job satisfaction, and intrinsic motivation. Employing established scales within a framework unifying CWB, intrinsic motivation, EI, organizational justice, and outcome constructs, two EI-based profiles displayed associations with CWB based on responses from 3,293 employees. Both the first core profile, high overall justice and low emotional intelligence, and the second core profile, high emotional intelligence and low work motivation, displayed associations with interpersonal deviance and organizational deviance, as well as emotional exhaustion and job satisfaction. The results are discussed with respect to possible underlying theory and an overarching unified motivation framework that incorporates goal choice, intrinsic motivation, antecedents, and outcomes. We also provide directions for future research and implications for managers in the workplace based on heuristic conceptual frameworks that combine multiple motivational perspectives into a unified model.